Multilobed propeller flap for reconstruction of popliteal fossa contractures: Case report - I. Ghorbel; F. Bouaziz; S. Moalla; Kh. Ennouri (Elsevier, 2019)
Post burn scar contractures of popliteal fossa may impair leg motion and have serious aesthetic effects.Through a case report, we present a scar contracture reconstruction of popliteal fossa using a multilobed propeller flap".This flap might be used to treat mild scar contractures with the presence of healthy skin around the recipient site. It allows restoring function, reconstruction with like to like skin and minimal donor site morbidity.Studies on large scale need to be conducted to demonstrate its superiority compared to other local flaps. Keywords: Post burn contractures, Popliteal fossa, Multilobed propeller flap